2020
DOI: 10.1111/1365-2745.13388
|View full text |Cite
|
Sign up to set email alerts
|

Do soil‐borne fungal pathogens mediate plant diversity–productivity relationships? Evidence and future opportunities

Abstract: From the establishment of the first biodiversity experiments in the 1990s, studies have consistently reported positive relationships between plant diversity and productivity in grasslands. However, the predominant hypotheses that may explain this pattern have changed. Initially, there was a strong focus on plant–plant interactions such as facilitation and resource partitioning, but the results from the first experiments that manipulated soil communities have led to a paradigm shift. In the current view on mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 105 publications
(136 reference statements)
0
44
0
Order By: Relevance
“…They also promote the water and minerals absorption by their host 5 . On the other hand, some of these fungi, especially pathogens, can strongly reduce their host productivity under certain conditions 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…They also promote the water and minerals absorption by their host 5 . On the other hand, some of these fungi, especially pathogens, can strongly reduce their host productivity under certain conditions 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In turn, recent studies have shown that these higher trophic levels, specifically pests and pathogens, play a major role in regulating the diversity of plant communities (Bever et al., 2015; Van der Putten et al., 2013). This has led to a shifted focus in biodiversity ecosystem functioning (BEF) studies: Where former explanations have been focussing on plant–plant interactions, the current focus is moving to plant–pathogen interactions (van Ruijven et al., 2020; Whitaker et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They certainly do. For instance, soil borne pathogens have been shown to be key drivers of plant succession and productivity in grassland biodiversity experiments (Ampt et al, 2019; Mommer et al, 2018; Van Ruijven et al, 2020). With a greater number of species, average productivity increases.…”
Section: Introductionmentioning
confidence: 99%